Mobile Application Development with Augmented Reality - Agarwal, Anmol; Sharma, Nitish Kumar; Gupta, Piyush; Saxena, Prakhar; Pal, Rohit Kumar; Mehrotra, Siddharth; Nair, Prabha; Wadhwa, Manoj (International Journal of Computer Sciences and Engineering, 2014)
Recently, because of the rapid development of mobile devices, augmented reality has extended from personal computers to mobile devices. They are getting popular as a platform for Augmented Reality (AR) application such as a Smartphone. The highly interactive nature of augmented reality with its user has given rise to various augmented reality applications for mobile devices, ranging from mere interaction to marketing, games, navigation, and so on. Mobile AR is mainly available whenever people require an informational support for a focused task. The combination of mobile applications and collaborative Augmented Reality into a single system makes the power of computer enhanced interaction and communication in the real world accessible anytime and everywhere. The objectives of the proposed work include main aspects of Augmented Reality (AR) for development of mobile applications. It describes the main fields in which mobile applications are developed using AR devices & systems. A mobile platform implementing the described features and collaboration between mobile and augmented reality is being demonstrated.